KAJIAN YURIDIS TERHADAP HUKUMAN KEBIRI PADA PELAKU PEMERKOSAAN TERHADAP ANAK (STUDI PUTUSAN NOMOR 695/PID.SUS/2019/PT SBY) - Muhammad Revio; Lola Yustrisia; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Abstract : The high rate of sexual violence against children perpetrated by perpetrators of sexual violence is a concern of every party, so in this case it can give a deterrent effect, so a rule of castration is made.Castration is a punishment for sex offenders, it is also a procedure for someone to remove the function of their testicles so that they cannot feel libido and become infertile. This castration has two different types of procedures. First with surgical procedures, second with chemical procedures, in surgical castration, or testicular surgery, the effects are permanent. But in chemical castration, drugs will be given periodically to reduce testosterone levels in the body, so that sex drive will decrease. The purpose of this research is to find out the arrangements for castration in Indonesia for perpetrators of the crime of rape against children and to find out the judge's considerations in making a decision in case Number 695/PID.SUS/2019/PT SBY. The method used is the normative legal research method, where this method is a legal research method that is only shown in written regulations so that this research is very closely related to the library because it will require library data. The data analysis used in this study is qualitative analysis. namely observing legal phenomena without using measuring instruments that produce numbers in the form of information that can only be assessed by using laws and regulations, theoretical views and conceptions, experts and logic, related to juridical studies of castration punishment for perpetrators of rape.Keywords: indonesian castration punishment, perpetrators of child rape, sexual violence.